2021
DOI: 10.3390/agronomy11122389
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Biochemical, and Metabolomic Strategies of the Date Palm (Phoenix dactylifera L., cv. Deglet Nour) Roots Response to Salt Stress

Abstract: Numerous Tunisian arid and semi-arid regions are subjected to soil salinity. Thus, they are known for halophytes plants cultivation, including date palms. Phoenix dactylifera L., cv. ‘Deglet Nour’, is a valuable Tunisian cultivar subjected to high salinity levels. In this way, our purpose is to evaluate the response of its roots to long period exposition to increasing salt concentrations. We started by studying the effects of 4 g/L, 8 g/L, 12 g/L, and 16 g/L NaCl on the parameters of germination (Growth rate—G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 92 publications
(97 reference statements)
1
7
0
Order By: Relevance
“…The halophytic nature of the date palm has been discussed and suggested by several studies, because of the palm's ability to tolerate high salinity levels [6,18,21,45,46]. The result obtained here shows a significant improvement in the biomass of young date palms, which can constitute a solid argument for this and confirm the salt-loving nature of this species, and even encourages a discussion on the type of halophyte it is, whether facultative or obligatory.…”
Section: Discussionsupporting
confidence: 70%
“…The halophytic nature of the date palm has been discussed and suggested by several studies, because of the palm's ability to tolerate high salinity levels [6,18,21,45,46]. The result obtained here shows a significant improvement in the biomass of young date palms, which can constitute a solid argument for this and confirm the salt-loving nature of this species, and even encourages a discussion on the type of halophyte it is, whether facultative or obligatory.…”
Section: Discussionsupporting
confidence: 70%
“…Studies conducted on Dendrobium officinale (Zhang, Yu, et al, 2021), Catharanthus roseus (Wang & Liu, 2010), and Date Palm (Bouhouch et al, 2021) have demonstrated that SS can lead to an increase in alkaloid compounds. Consistent with these findings, our study revealed that out of the 30 DAMs in the Salt versus CT comparison, 16 were upregulated in the alkaloid category.…”
Section: Discussionmentioning
confidence: 99%
“…Salt stress is one of the most important threats to agricultural production and food security. For more than 3000 years, it has been a threat to agriculture in many regions of the world [1][2][3][4][5][6]. Globally, 22% of the total arable land and 33% of the total irrigated agricultural area are under salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Osmotic pressure leads to nutritional imbalance, morphological damage and reduced photosynthesis. This leads to a decline in growth and productivity, which can lead to cell death [3,9]. Like many other abiotic stresses, salt stress restricts plant growth by increasing soil osmotic potential and reducing water uptake through the roots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation